2021
DOI: 10.1016/j.neo.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2-mediated direct phosphorylation regulates YAP activity promoting glioblastoma growth and invasive characteristics

Abstract: The Hippo and mTOR signaling cascades are major regulators of cell growth and division. Aberrant regulation of these pathways has been demonstrated to contribute to gliomagenesis and result in enhanced glioblastoma proliferation and invasive characteristics. Several crosstalk mechanisms have been described between these two pathways, although a complete picture of these signaling interactions is lacking and is required for effective therapeutic targeting. Here we report the ability of mTORC2 to directly phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Indeed, mTORC2 subunit is able to phosphorylate YAP on serine 436 (Ser436) allowing the activation of the Hippo signaling independently from the canonical pathway. This aberrant interplay promotes growth, migration, and drug resistance in both cell lines and GBM patient samples [23][24][25].…”
Section: Glioblastoma Chemoresistancementioning
confidence: 99%
“…Indeed, mTORC2 subunit is able to phosphorylate YAP on serine 436 (Ser436) allowing the activation of the Hippo signaling independently from the canonical pathway. This aberrant interplay promotes growth, migration, and drug resistance in both cell lines and GBM patient samples [23][24][25].…”
Section: Glioblastoma Chemoresistancementioning
confidence: 99%
“…In our experimental model, the exposure of A549 and Calu-1 cell lines to the combination of the previously mentioned cytokines induced the activation of the autophagic process, the concurrent mTORC2-AKT pathway downregulation and modulation of YAP expression. Numerous studies have shown a complex crosstalk between the mTOR kinase signaling pathway and YAP, suggesting that YAP and mTOR proteins, by regulating each other, may contribute to cancer progression [ 99 , 100 ]. Furthermore, it has been reported that although YAP controls autophagic flux by regulating the autophagosomes’ turnover, transcriptional YAP activity is also essential for the maturation of autophagosomes into autolysosomes [ 30 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of ERK Ser-249 and Ser-266 phosphorylation might affect the occurrence of glioma through Aml1/Runx1 [ 59 ]. Ser-436 phosphorylation promoted YAP-mediated GBM proliferation, migration, and invasion [ 60 ]. NDR1 inhibited GBM progression by phosphorylating YAP [ 61 ].…”
Section: Discussionmentioning
confidence: 99%